Applying Songs for Listening Comprehension and Learning Motivation in Preparing National Examination at MA Maarif 06 Pasir Sakti - Eka Pra Setiyawati (Premise: Journal of English Education and Applied Linguistics, 2016)
This research discusses about the effectiveness of song towards the students’ listening comprehension and their learning motivation for National Examination preparation in secondary school. The teacher applied the particular songs at beginning of listening class to attract and increase the students’ listening ability. This research was Classroom Action Research and the data was taken with tests and questionnaires. The subject of the research was 28 students of grade twelve (Science class) who are going to do National Examination. The teacher targetted 75% of students exceed 20 score or more from maximum score 30 in listening section. The result showed that the students’ listening comprehension was increased significantly. It could be seen from pre-liminary cycle was 11%, in cycle 1 was 60%, and in cycle 2 was 75% of students got the minimum score of 20. The students’ learning motivation was also improved as their listening achievement. Therefore, the teacher believed that a song can improve the students’ listening comprehension and their learning motivation.